Media and security forces. The media treatment of cases of police violence during the pandemic in Buenos Aires Metropolitan Area (Delito y Sociedad, 2022)
This article analyzes the media treatment of cases of harassment and homicide produced by police and gendarmes towards young people during the Covid-19 pandemic in the Metropolitan Area of Buenos Aires. The aim is to identify the characteristics of the particular circumstances in which these events take place, the roles and responsibilities attributed to their protagonists in the country’s main digital media. To this end, the methodological approach combines quantitative and qualitative techniques. First, we systematized all mediated cases of police violence between March 2020 and March 2021. Secondly, from the selection of a set of paradigmatic cases, we analyzed the informative coverage on the modalities of intervention of the security forces in Clarín, La Nación, Página 12 and Infobae. Some results allow us to affirm that the informative treatment of homicide cases produced by police officers was legitimized in the media based on arguments linked to the violation of the victim’s control measures for the enforcement of quarantine, in contrast to cases of harassment in which the media denounced police violence for exceeding the frameworks of preventive and compulsory social isolation.
Keywords: media; security forces; violence; youths